Adaptive Digital Capability Development: Professional Learning for Educators Across Disciplines - Peterson, J; Lockhart, C; Raffaele, C (Academy for Design Innovation Management, 2019)
In a cross-university project, a mixed methods approach was adopted to design a learning model for digital work practices in line with evolving industry needs. Drawing upon industry input (n=50), developmental learning and technology affordance theory, a model was trialled with Design, Journalism and Engineering students (n=78). Workshops were held at five universities with educators (n=66) and this paper discusses their perspectives on the model. Their responses indicated a predominantly functional digital capability focus in their current learning and teaching practice; rather than integrating functional, perceptual and adaptive digital capabilities, which are in high demand but short supply in industry. The educators highlighted a need for their own professional learning and we offer practical suggestions for moving beyond a functional digital focus. We argue it is vital for students and educators to learn and use the vocabulary of technology affordances, to strengthen professional learning for digital work futures.
Keywords: Digital enterprise learning; Adaptive capability; Technology affordances; Professional learning; Academic development